Decolonizing Game Literacy - Robinson, Petra A.; Williams, Kamala V.; Stojanović, Maja; Paula, Bruno de (Global Citizenship for Adult Education: Advancing Critical Literacies for Equity and Social Justice, 2022)
In the last decades, digital games have moved from niche to mainstream. As more people play, talk about, and engage with these artifacts, they have become an important part of contemporary cultures, giving rise to game literacy—the set of skills needed to meaningfully engage with video games. While the potentials of game literacy have, to some extent, been already discussed in the literature, we have not adequately discussed the need for a game literacy that problematizes the sociocultural dimensions of gaming, including the hegemonic, exclusionary rationales implicitly disseminated through mainstream gaming. In this chapter, I outline a decolonial model for game literacy, remarking how the reflection about the gaming circuits of production and dissemination should be part of any initiative that aims at dealing with critical and creative competences towards gaming, and how these are crucial for any citizen in contemporary societies.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Décentrer l’histoire du jeu vidéo ? - Derfoufi, Mehdi (De l'autre côté, 2018)
Peut-on envisager une autre histoire du jeu vidéo ?
Keywords: 1-Jeux vidéo; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Identités diasporiques; _Nettoyé

Woke Gaming: Digital Challenges to Social Injustice - Gray, Kishonna L.; Leonard, David J. (University of Washington Press, 2018)
From #Gamergate to the daily experiences of marginalization among gamers, gaming is entangled with mainstream cultures of systematic exploitation and oppression. Whether visible in the persistent color line that shapes the production, dissemination, and legitimization of dominant stereotypes within the industry itself, or in the dehumanizing representations often found within game spaces, many video games perpetuate injustice and mirror the inequities and violence that permeate society as a whole. Drawing from the latest research and from popular games such as World of warcraft and Tomb raider, Woke gaming examines resistance to spaces of violence, discrimination, and microaggressions in gaming culture. The contributors of these essays identify strategies to detox gaming culture and orient players toward progressive ends, illustrating the power and potential of video games to become catalysts for social justice
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Méthodologie de recherche décoloniale; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé

Introduction to the Special Issue on Postcolonial Perspectives in Game Studies - Mukherjee, Souvik; Hammar, Emil Lundedal (Open Library of Humanities, 2018)
The treatment of colonialism in video games, barring a few notable exceptions, is marked by a Western and, specifically, late 19th-century imperialist bias. Simultaneously, in the past two decades of multifaceted research and the development of robust theoretical frameworks in the still fledgling discipline of game studies, postcolonial discourses, whether they comprise critiques of imperialism or neocolonialism, have not been prominently highlighted until very recently. A coherent effort to bring together the current research on postcolonialism in video games was also urgently required. Further, the past years has seen a rather persistent, albeit unexpected, emergence of a pro-colonial or pro-imperialist discourse in mainstream academia that even justifies the continuance of empire as an ameliorating influence on the people of the so-called developing countries, most of which had formerly been colonized by European powers.Thus, it is the aim of this issue to address this epistemic omission and counter such bias where it exists by also bridging video games research with larger discussions of postcolonialism in other humanities contexts and disciplines. The various articles in this special issue offer a range of perspectives from epistemological power to theory and praxis in critical academia, to contexts of production and practices of play, to close readings of postcolonial traces in video games. These varying approaches to the analysis of video games and their societal and historical contexts open up the debates further to a diverse set of topics ranging from board games to phone games or from mainstream high-budget console games to indie titles that question colonialism. As video games address issues relating to orientalism, subalternity, and hybridity as well as the current ambiguities in conceiving nationhood and the postcolony, the articles in this issue will also likely adumbrate further serious commentary that will develop both game studies research and current conceptions of the postcolonial.
Keywords: 1-Jeux vidéo; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Queerness in Play - Harper, Todd; Adams, Meghan Blythe; Taylor, Nicholas (Palgrave Macmillan, 2018)
"Queerness in Play examines the many ways queerness of all kinds - from queer as 'LGBT' to other, less well-covered aspects of the queer spectrum - intersects with games and the social contexts of play. The current unprecedented visibility of queer creators and content comes at a high tide of resistance to the inclusion of those outside a long-imagined cisgender, heterosexual, white male norm. By critically engaging the ways games - as a culture, an industry, and a medium - help reproduce limiting binary formations of gender and sexuality, Queerness in Play contributes to the growing body of scholarship promoting more inclusive understandings of identity, sexuality, and games."--Provided by publisher.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Méthodologie de recherche décoloniale; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé